2014
DOI: 10.1536/ihj.13-297
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Circumferential Endocardial Extent of Myocardial Edema and Infarction in Patients With Reperfused Acute Myocardial Infarction

Abstract: SummaryT2 weighted (T2W) images on cardiovascular magnetic resonance (CMR) visualizes myocardial edema, which refl ects the myocardial area at risk (AAR) in reperfused acute myocardial infarction (AMI). Late gadolinium enhancement (LGE) demonstrates myocardial infarction.LGE images cover the whole left ventricle, but T2W images are obtained from a few slices of the left ventricle due to the long sequence time, so the quantifi cation of AAR of the entire left ventricle is diffi cult. We hypothesize that we can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…19,20) STEMI itself can introduce infarction related no reflow, which is caused by myocardial ischemia-reperfusion injury, endothelial damage, and other consequences. Stent implantation can cause intervention related no reflow.…”
Section: Discussionmentioning
confidence: 99%
“…19,20) STEMI itself can introduce infarction related no reflow, which is caused by myocardial ischemia-reperfusion injury, endothelial damage, and other consequences. Stent implantation can cause intervention related no reflow.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] However, due to limitations in spatial resolution, the imaging of the thinner atrial wall is more challenging. Recent advancements in MRI techniques have provided higher-resolution images that enable the localization and quantification of atrial SRM.…”
Section: Discussionmentioning
confidence: 99%
“…8,9) The utility of LGE-MRI to characterize ventricular myocardial injury has been confirmed using comprehensive pathological validation studies, and the method is now widely used in clinical practice. [9][10][11][12] Several recent pilot studies that involved electrical and/or pathological validation have reported that cardiac MRI is useful for characterizing transcatheter ablation-induced atrial scar tissue in animal models. 8,13) However, no fundamental pathological validation study has been conducted on the use of cardiac LGE-MRI for the assessment of pre-ablation LA-SRM in AF patients.…”
mentioning
confidence: 99%
“…A clinically relevant phenomenon that occurs is myocardial ischemia/reperfusion (I/R) injury, which refers to damage to the myocardial structure after regaining blood perfusion to the ischemic myocardium (5). Cardiac muscle cells may also die and the area of myocardial necrosis may extend, which seriously affects the prognosis of patients with myocardial infarction (6). In clinical practice, myocardial I/R injury may result in the disorder of electrical activities in the myocardium, arrhythmia and cardiac insufficiency (7).…”
Section: Introductionmentioning
confidence: 99%